Undated letter from Carl Duncan to Patricia Whiting - Duncan, Carl D. (Carl Dudley), 1895-1966:::Creator::::::::::::
A note originally attached to a magazine or newspaper that probably discussed the 1965 obscenity trial of Ralph Ginzburg.